2022
DOI: 10.3390/s22176340
|View full text |Cite
|
Sign up to set email alerts
|

Piezoresistance Characterization of Silicon Nanowires in Uniaxial and Isostatic Pressure Variation

Abstract: Silicon nanowires (SiNWs) are known to exhibit a large piezoresistance (PZR) effect, making them suitable for various sensing applications. Here, we report the results of a PZR investigation on randomly distributed and interconnected vertical silicon nanowire arrays as a pressure sensor. The samples were produced from p-type (100) Si wafers using a silver catalyzed top-down etching process. The piezoresistance response of these SiNW arrays was analyzed by measuring their I-V characteristics under applied uniax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…Resistance increments upon different humidity variations indicate that the observed response was a combined result of both pressure and humidity variation. This result was also in good agreement with our previous study on the PZR effect on SiNWs [ 17 ]. We investigated the iso-static pressure variation effect on SiNWs and observed a dramatic increase in resistance by more than two orders of magnitude when pumping the air out of the vacuum chamber and decreasing the humidity and pressure.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Resistance increments upon different humidity variations indicate that the observed response was a combined result of both pressure and humidity variation. This result was also in good agreement with our previous study on the PZR effect on SiNWs [ 17 ]. We investigated the iso-static pressure variation effect on SiNWs and observed a dramatic increase in resistance by more than two orders of magnitude when pumping the air out of the vacuum chamber and decreasing the humidity and pressure.…”
Section: Resultssupporting
confidence: 93%
“…Our previous study showed that hydrogenation on p-type SiNWs dramatically decreased its sensitivity. As hydrogenation is known to passivate shallow and deep defects in both n and p-type Si, these results strongly indicate that surface states play a significant role in the PZR effect [ 17 ]. Surface states of the SiNWs may also play an important role in the humidity-sensing mechanism described in a review article by Akbari-Saatlu et al for metal-oxide semiconductors [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these nanostructures, nanowires have attracted considerable attention due to their potential applications in modern technologies. Nanowires of small size are ideal for miniaturized devices such as transistors [1], batteries [2], and sensors [3,4]. Also, their high surface area to volume ratio increases the efficiency of energy storage, and provides unique physical and chemical properties such as improved electrical conductivity, increased strength, and enhanced catalytic activity [5][6][7].…”
Section: Introductionmentioning
confidence: 99%